2006
DOI: 10.1667/rr0524.1
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms of Nonhomologous End Joining in the Repair of Site-Directed Chromosomal Breaks with Noncomplementary and Complementary Ends

Abstract: DNA double-strand breaks (DSBs) are considered the most important type of DNA damage inflicted by ionizing radiation. The molecular mechanisms of DSB repair by nonhomologous end joining (NHEJ) have not been well studied in live mammalian cells, due in part to the lack of suitable chromosomal repair assays. We previously introduced a novel plasmid-based assay to monitor NHEJ of site-directed chromosomal I-SceI breaks. In the current study, we expanded the analysis of chromosomal NHEJ products in murine fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…We stably integrated a single copy of the NHEJ substrate pHW1 in which the two I-SceI sites are separated by 30 base pairs of intervening sequence (29,30) into the genome of HEK293 cells. A pair of primers flanking the two I-SceI sites and a probe complementary to the sequence resulting from precise end joining was designed for quantitative real-time PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We stably integrated a single copy of the NHEJ substrate pHW1 in which the two I-SceI sites are separated by 30 base pairs of intervening sequence (29,30) into the genome of HEK293 cells. A pair of primers flanking the two I-SceI sites and a probe complementary to the sequence resulting from precise end joining was designed for quantitative real-time PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Strategy for NHEJ Assays-Methods for analysis of precise NHEJ have been reported previously (29). Forty-eight hours after I-SceI expression, genomic DNA was extracted with Qiagen's DNeasy kit for real-time PCR analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A substrate with a closer I-SceI site has also been described (39). We have shown that the I-SceI-excised fragment can be inverted or translocated and captured at a third DSB (1).…”
Section: Discussionmentioning
confidence: 96%
“…To explore further the mechanisms that regulate NHEJ subpathways, we have used an assay to create site-specific DSBs within the chromosomally integrated NHEJ substrate pPHW1 in HEK293 cells (32,33), which produces fully complementary cohesive ends. We showed that both precise C-NHEJ and imprecise D-NHEJ pathways are utilized to repair the DSBs in this setting, consistent with a previous observation (33). When the DNA damage response protein Mre11 was silenced, there was an ϳ10 -12-fold reduction in small sequence deletions at the break junction compared with the levels of D-NHEJ in siRNA control cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the NHEJ substrate and the strategy to measure NHEJ were described previously (9,32,33) and are depicted in Rejoining of the double-stranded ends by either precise C-NHEJ or error-prone D-NHEJ will reconstitute translation of the gpt ORF, permitting cell survival under XHATM selection and detection of recombinants as colonies grown in XHATM selection medium. Alternatively, error-prone D-NHEJ at either of the single I-SceI sites can also disrupt ATG ART , allowing again for selection of recombinants with XHATM.…”
Section: Strategy and Generation Of The Hek293/pphw1 Cell Line-mentioning
confidence: 99%